If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 9)(x + 2) = 2x Reorder the terms: (9 + x)(x + 2) = 2x Reorder the terms: (9 + x)(2 + x) = 2x Multiply (9 + x) * (2 + x) (9(2 + x) + x(2 + x)) = 2x ((2 * 9 + x * 9) + x(2 + x)) = 2x ((18 + 9x) + x(2 + x)) = 2x (18 + 9x + (2 * x + x * x)) = 2x (18 + 9x + (2x + x2)) = 2x Combine like terms: 9x + 2x = 11x (18 + 11x + x2) = 2x Solving 18 + 11x + x2 = 2x Solving for variable 'x'. Reorder the terms: 18 + 11x + -2x + x2 = 2x + -2x Combine like terms: 11x + -2x = 9x 18 + 9x + x2 = 2x + -2x Combine like terms: 2x + -2x = 0 18 + 9x + x2 = 0 Factor a trinomial. (6 + x)(3 + x) = 0Subproblem 1
Set the factor '(6 + x)' equal to zero and attempt to solve: Simplifying 6 + x = 0 Solving 6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + x = 0 + -6 x = 0 + -6 Combine like terms: 0 + -6 = -6 x = -6 Simplifying x = -6Subproblem 2
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Solution
x = {-6, -3}
| -8(2n-1)=104 | | 20=6-7x-7 | | 99=2n-5(3n+1) | | 6(2x-8)=3(3x-9) | | -8(6m-6)-8m=440 | | x^2+7x+K=0 | | -(156x-13)= | | hg(x)=3.08(x)sqrt+18.97 | | 232=4(8n-6) | | 100=4(4-3x) | | -(156-13)= | | 95=5(4-3n) | | 2.28x-.8=2x+1.8 | | Hg(x)=3.08(52)sqrt+18.97 | | -5(-1-2p)+5p=95 | | .8x+.2=.6x+-10 | | 3x-7-x=5x+14 | | 6y-10=2+4y | | 5x-11=4x+7 | | -217=-6(-6v-6)-1 | | 6(7+3x)=150 | | 0=-5n-2m | | 18x+21=10x+90 | | -317=3+5(8k-8) | | 9y-3=4+2y | | X=3xj-4 | | 4x+7(1-5x)=-210 | | (-9,2)(-10,-4)= | | 4x^2+4x+9=0 | | 7m=5+8m | | 9t-14=-26+5t | | 3(k+2)=21 |